The IMF's provision of insurance against balance of payments needs and how to improve it - Klaus Ruhlmann (Danmarks Nationalbank, 2021)
The memo summarizes the design and use of the IMF's precautionary facilities since their introduction and discusses lessons and potential reform options. In particular, the framework for these facilities should be adjusted to address prolonged use at high access levels.
Keywords: 330; Zahlungsbilanz; IWF-Kredit; Welt